Eutrophication triggers diel and seasonal shifts of carbon dioxide and oxygen in tropical urban coastal waters - Tainan da Fonseca Fernandes; Roberta Bittencourt Peixoto; Luana Queiroz Pinho; Letícia Cotrim daCunha; Thiago Veloso Franklin; Ricardo César Pollery; Vinícius Peruzzi de Oliveira; Leonardo Amora‐Nogueira; Humberto Marotta (Limnology and Oceanography Letters)
Abstract Coastal waters play a pivotal role in the global carbon cycle, showing increased short‐term variability of dissolved oxygen saturation (DOsat) and partial pressure of greenhouse gases like carbon dioxide (pCO2), especially in underrepresented tropical eutrophic environments. Here, we conducted high‐frequency (1‐min interval) diel measurements of surface DOsat and pCO2 in Guanabara Bay, Brazil, a highly nutrient‐enriched coastal ecosystem. The predominant metabolic controls on pCO2 were revealed by its strong negative correlation with DOsat. Air–sea CO2 fluxes derived from high‐frequency diel sampling showed emissions of 533 mmol C m−2 annually. Conventional estimates based on daylight‐only measurements were ~73% and 319% higher in the morning (10:00–12:00 h and sunrise–8:00 h, respectively) or ~172% and 244% lower in the afternoon (12:00–14:00 h and 14:00–16:00 h, respectively). Our findings indicate that rapid diel shifts between CO2 sinks and sources in eutrophic coastal waters can introduce significant uncertainty in estimating air–water CO2 fluxes from regional to global carbon budgets.